2008
DOI: 10.1128/jb.00748-08
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Assessment of the Regulons Controlled by the FixLJ-FixK2-FixK1Cascade inBradyrhizobium japonicum

Abstract: Symbiotic N 2 fixation in Bradyrhizobium japonicum is controlled by a complex transcription factor network. Part of it is a hierarchically arranged cascade in which the two-component regulatory system FixLJ, in response to a moderate decrease in oxygen concentration, activates the fixK 2 gene. The FixK 2 protein then activates not only a number of genes essential for microoxic respiration in symbiosis (fixNOQP and fixGHIS) but also further regulatory genes (rpoN 1 , nnrR, and fixK 1 ). The results of transcrip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
197
0
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 116 publications
(209 citation statements)
references
References 67 publications
10
197
0
2
Order By: Relevance
“…S1, lanes 1-3). This result was unexpected, because previous studies showed a clear induction of fixK 2 gene expression in response to decreased oxygen concentrations, although a basal level of fixK 2 expression had been noticed even in aerobiosis (16,17,20 H2O2 sensitivity of the B. japonicum WT and the C183A-FixK2-expressing mutant strain 8854. Soft agar (0.9%) plates with PSY medium were inoculated with the indicated B. japonicum strains.…”
Section: Analysis Of the In Vivo Status Of The Fixk2mentioning
confidence: 80%
See 2 more Smart Citations
“…S1, lanes 1-3). This result was unexpected, because previous studies showed a clear induction of fixK 2 gene expression in response to decreased oxygen concentrations, although a basal level of fixK 2 expression had been noticed even in aerobiosis (16,17,20 H2O2 sensitivity of the B. japonicum WT and the C183A-FixK2-expressing mutant strain 8854. Soft agar (0.9%) plates with PSY medium were inoculated with the indicated B. japonicum strains.…”
Section: Analysis Of the In Vivo Status Of The Fixk2mentioning
confidence: 80%
“…Signal intensity detection, normalization and statistical analysis were done as already established (17,45). Only those probe sets that were called ''present'' or ''marginal'' in Ն67% of the replicates of each experiment were considered for further analysis.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, if the early increase in phaC2 transcript levels observed in this study results in a later increase in PhaC2 protein levels, this paralog would soon occupy the limited PhaC sites on the granule surface, thus disturbing the access of PhaC1, which might lead to a diminished biosynthetic activity, or it may preclude the access of a PHA depolymerase enzyme. The interplay between PhaC1 and PhaC2 might be relevant in nodules, where phaC2 expression is stimulated 6-fold by FixK2 (a transcription factor enhancer that is stimulated by low O 2 levels) (10). Surprisingly, phaC3, which was poorly expressed in the wild type, was upregulated at logarithmic growth phase in the ⌬phaC2 mutant.…”
Section: Discussionmentioning
confidence: 99%
“…Escherichia coli strains grew in LB medium (18) at 37°C with the following antibiotics, added at the indicated final concentrations: ampicillin at 200 g/ml in solid medium and 100 g/ml in liquid medium, gentamicin at 10 g/ml, hygromycin B at 200 g/ml, kanamycin at 30 g/ml, streptomycin at 50 g/ml, and tetracycline at 10 g/ml. We cultivated B. diazoefficiens strains at 30°C in PSY medium (19) supplemented with 0.1% L-(ϩ)-arabinose and the following antibiotics at the indicated concentrations: chloramphenicol at 20 g/ml (for counterselection of E. coli), hygromycin B at 200 g/ml, kanamycin at 100 g/ml, spectinomycin at 100 g/ml, and tetracycline at 50 g/ml (solid medium) and 25 g/ml (liquid medium). Rhodopseudomonas palustris strains grew at 30°C in modified YPMS medium (20) (which has the same trace elements that exist in PSY medium) containing gentamicin where appropriate (800 g/ml for initial selection and 400 g/ml for routine cultures).…”
Section: Methodsmentioning
confidence: 99%